Kompetensi Jurnalis Sebagai Aktor Dalam Produksi Berita Media Multiplatform - Udi Rusadi (BPSDMP Kominfo Jakarta, 2012)
Innovations in the field of information and communication technology have created the variety of information distribution platform to audiences. This is prompted media companies to build and effort to develop system management of news production multiplatform which intended as an effort to keep the media companies alive and growing. By using framework of structuration theory, the pourpose of this study is to reveal the relationship between structure and agency of journalist as actor. The method used is a case study in media companies in South Kalimantan, Banjarmasin Post. The results showed that the duality of structure occurs, which the structure always provides the enabling and the obviouslimitations that cause system technology based newsproduction run. In line with the sructure roles, journalists as human actors adjust their competences with management system multiplatform. The system running by the developing of individual basic competences include discursive and practical consciousness, cognitive motivation and soft competences of online media namely attitude of speedy and multi-tasking working and having the work orientation of social networking. Inovasi teknologi komunikasi dan informasi menumbuhkan aneka ragam platform distribusi informasi kepada khalayaknya. Hal ini mendorong perusahaan media membangun dan berusaha mengembangkan sistem manajemen produksi berita multiplatform agar perusahaan media tetap eksis. Dengan kerangka pemikiran teori strukturasi, studi ini bertujuan mengungkap keterkaitan antara struktur dan agensi dari para jurnalis sebagai aktor. Metode yang digunakan ialah studi kasus di perusahaan media Banjarmasin Post di Kalimantan Selatan. Hasilnya menunjukkan, dualitas struktur terjadi, dimana struktur selalu memberikan pemungkin (enable) dan batasan-batasan yang jelas yang menyebabkan sistem produksi berita berbasis teknologi dijalankan. Sejalan dengan peranan struktur tersebut, para jurnalis sebagai human actormenyesuaikan kompetensinya dengan sistem manajemenmultiplatform yaitu menjalankan struktur dengan mengembangkan kompetensi dasar meliputi kesadaran diskursif, praktis dan motivasi kognitif dan mengembangkan kompetensi lunak media onlineyaitu sikap kerja cepat, multitaskingdan memiliki orientasi kerja berjejaring sosial.